A full-spectrum Boswellia serrata extract with enhanced bioavailability, and its co-delivered system with curcumin alleviate pain and stiffness associated with moderate spondylitis: a randomized double-blind, placebo-controlled, 3-arm study - Mamatha, K.; Prabhakaran, Prathibha; Syam Das, S.; Kanjoormana Aryan, Manu; Thomas, Jestin (Frontiers in Pharmacology, 2025)
ObjectivePain and stiffness at the neck, back, hip, and other joints due to conditions such as spondylitis or spondylosis are significant musculoskeletal concerns globally. The present study evaluated the relative efficacy of a bioavailability enhanced full-spectrum extract of Boswellia serrata Roxb. oleo-gum resin (F-BSE) and its co-delivery system with curcumin (C-BSE) in ameliorating pain and stiffness, in otherwise healthy participants.MethodsThis study adopted a randomized, double-blind, placebo-controlled, three-arm, parallel group comparative design. The participants received the placebo, F-BSE, or C-BSE for 28 days at the dose of 400 mg/day. The efficacy was assessed using subjective tools [Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Neck Disability Index (NDI) questionnaires) and objective measures (clinical markers, NLRP3 and IL-1β).ResultsA total of 105 participants (n = 35/group) were recruited, of which 94 completed the 28-day study period. Both the F-BSE and C-BSE groups showed significant reductions in pain, stiffness, and neck-related disability, as reflected in the BASDAI and NDI scores. Additionally, NLRP3 inflammasome and IL-1β levels were significantly reduced by days 14 and 28. These outcomes suggest that the combined administration of curcuminoids and boswellic acids with improved bioavailability modulates inflammatory pathways, thus contributing to symptom relief and improved function.ConclusionBoth F-BSE and C-BSE reduced pain and stiffness issues by day 14, which continued to progress through day 28. However, C-BSE demonstrated superior effects compared to F-BSE, indicating a synergistic anti-inflammatory and analgesic action when the full-spectrum Boswellia extract and curcumin are delivered as a water-soluble, non-covalent complex with enhanced bioavailability using the FenuMat® delivery technology.Clinical trial registrationhttps://ctri.nic.in/Clinicaltrials/pmaindet2.php?EncHid=NjI2MTY=&Enc=&userName=, identifier: CTRI/2021/12/038613 dated 14/12/2021.